2014
DOI: 10.1016/j.joca.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Defective autophagy in chondrocytes with Kashin-Beck disease but higher than osteoarthritis

Abstract: Autophagy was defective in KBD chondrocytes, but it was higher than in OA. The insufficient autophagy may be associated with apoptosis and mitochondrial change in the pathogenesis of KBD and OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 39 publications
2
34
1
Order By: Relevance
“…The present study showed that several mRNA (MMP-9, MMP-13, BMP-2 and ADAMTS5) are up-regulated and one mRNA (COL2A1) down-regulated in OA compared with normal cartilage. Our findings concerning expression of mRNA are consistent with those of previous studies of OA [27][28][29] . Thus, the present RT-PCR results supported cartilage degeneration in the OA group.…”
Section: Discussionsupporting
confidence: 93%
“…The present study showed that several mRNA (MMP-9, MMP-13, BMP-2 and ADAMTS5) are up-regulated and one mRNA (COL2A1) down-regulated in OA compared with normal cartilage. Our findings concerning expression of mRNA are consistent with those of previous studies of OA [27][28][29] . Thus, the present RT-PCR results supported cartilage degeneration in the OA group.…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, autoghagy can degrade these molecules, inhibiting chondrocyte apoptosis and blocking the degeneration of articular cartilages and OA development [52][53][54]. Additionally, evidence showed that ROS also interacted with autophagy during the degenerative process of cartilages [55,56]. Wu Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry et al [56] found that OA chondrocytes had lower autophagic level and higher level of ROS production compared with the normal chondrocytes.…”
Section: Ampk/mtor Signaling Pathway Is Involved In Gapn-induced Automentioning
confidence: 99%
“…Additionally, evidence showed that ROS also interacted with autophagy during the degenerative process of cartilages [55,56]. Wu Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry et al [56] found that OA chondrocytes had lower autophagic level and higher level of ROS production compared with the normal chondrocytes. Cetrullo et al [57] demonstrated that oxidative stress inhibited the expression of autophagy-related proteins in chondrocytes and promoted apoptosis.…”
Section: Ampk/mtor Signaling Pathway Is Involved In Gapn-induced Automentioning
confidence: 99%
“…According to a previous method [], the samples in different groups were cut into 1.0‐mm 3 sections, rinsed with PBS, fixed in 2.5% glutaraldehyde at 4°C overnight, and then embedded in epoxy resin. The samples were sectioned into 20‐30 nm slices for transmission electron microscopy (TEM) analysis.…”
Section: Methodsmentioning
confidence: 99%